2019
DOI: 10.1111/jfbc.13062
|View full text |Cite
|
Sign up to set email alerts
|

Egg white hydrolysates improve vascular damage in obese Zucker rats by its antioxidant properties

Abstract: Metabolic Syndrome (MS) is related to increased risk of early death due to cardiovascular complications, among others. Dietary intervention has been suggested as the safest and most cost‐effective alternative for treatment of those alterations in patients with MS. The aim of this study was to investigate the effects of different egg white hydrolysates (HEW1 and HEW2) in obese Zucker rats, focus on the development of cardiovascular complications. Blood pressure, heart rate, basal cardiac function and vascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Egg white hydrolysate derived from hydrolysis with pepsin for 8 h has several biological activities, such as antioxidant, free radical scavenger, ACE inhibitor, vascular-relaxing, and anti-inflammatory ( Miguel et al, 2004 ). Fourteen of its constituent peptides have been identified (FRADHPFL, RADHPFL, YAEERYPIL, YRGGLEPINF, ESIINF, RDILNQ, IVF, YQIGL, SALAM, and FSL; Davalos et al, 2004 ; Miguel et al, 2004 ; Garcés-Rimón et al, 2016 ) and their biological actions have been previously reported in vitro or in vivo studies ( Miguel et al, 2006 , 2007 ; Garces-Rimon et al, 2019 ). However, these peptides and amino acids act individually, cooperatively, and synergistically; during their passage through the gastrointestinal tract, some modifications due to new hydrolysis should be considered ( Miner-Williams et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Egg white hydrolysate derived from hydrolysis with pepsin for 8 h has several biological activities, such as antioxidant, free radical scavenger, ACE inhibitor, vascular-relaxing, and anti-inflammatory ( Miguel et al, 2004 ). Fourteen of its constituent peptides have been identified (FRADHPFL, RADHPFL, YAEERYPIL, YRGGLEPINF, ESIINF, RDILNQ, IVF, YQIGL, SALAM, and FSL; Davalos et al, 2004 ; Miguel et al, 2004 ; Garcés-Rimón et al, 2016 ) and their biological actions have been previously reported in vitro or in vivo studies ( Miguel et al, 2006 , 2007 ; Garces-Rimon et al, 2019 ). However, these peptides and amino acids act individually, cooperatively, and synergistically; during their passage through the gastrointestinal tract, some modifications due to new hydrolysis should be considered ( Miner-Williams et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies point out the beneficial effects of consuming different natural antioxidant compounds and bioactive food ingredients, such as protein-derived peptides against oxidative imbalance ( Serafini and Peluso, 2016 ; Peluso and Serafini, 2017 ; Chikara et al, 2018 ). Bioactive peptides from egg white hydrolysate (EWH) have shown important antioxidant properties, preventing dysfunction in hypertensive and obese experimental models ( Manso et al, 2008 ; Garces-Rimon et al, 2019 ). We propose to use EWH obtained after hydrolysis of hen egg white with pepsin for 8 h, which has previously demonstrated antioxidant, anti-inflammatory, and angiotensin-converting enzyme (ACE) inhibitory properties ( Miguel et al, 2004 ; Moreno-Fernandez et al, 2018a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, egg white peptides ameliorated oxidative stress and hyperlipidemia in hypertensive rats (40). Also, Garcés-Rimón et al (43) demonstrated that bioactive peptides of egg white exerted strong antioxidant effects leading to prevention of abnormalities in experimental models that are obese and hypertensive. On the other hand, enzymatic hydrolysate of lysozyme produced LPH2, showing a strong ACE inhibitory effect, high antioxidant activity in ORAC-Fl assay, and resistance to gram-negative and gram-positive bacteria (48).…”
Section: Beneficial Effects Of Albumen On Human Health and The Food I...mentioning
confidence: 96%
“…Hydrolysis of albumen proteins yields peptides with strong antioxidant capacity. Alcalase peptide with the sequence (Tyr-Ala-Glu-Glu-Arg-Tyr-Pro-Ile-Leu) has a high antioxidant capacity and free radical scavenging ability (21,43). In addition, peptides with the sequence (Try-Leu-Gly-Ala and Lys) and (Gly-Gly-Leu-Glu-Pro-Ile-Phe-Glu) exhibited significant antioxidant effects in 2,2diphenyl-1-picrylhydrazyl radical scavenging capacity (DPPH) and lipid peroxidation inhibition assays (44).…”
Section: Beneficial Effects Of Albumen On Human Health and The Food I...mentioning
confidence: 99%
“…119,120 In addition, feeding mice with 750 mg/kg of egg white hydrolysate daily from the 8th week to the 20th week (n = 10) increased the body's antioxidant status by increasing the bioavailability of NO, reducing the expression of NOX-1 and the production of superoxide anions. 121 Angiotensin II mediates many cellular activities including stimulating the formation of intracellular ROS, thereby participating in the increase of oxidative stress. 122 Therefore, spontaneously hypertensive rats are not only recognized as a human primary hypertension model but also as an oxidative stress model.…”
Section: Antioxidant Stress Activitymentioning
confidence: 99%